2022
DOI: 10.1002/app.52395
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic toughening of polypropylene by thermoplastic starch acetate andSEBS‐MAH

Abstract: The plasticized starch exhibits flexible properties, similar to that of elastomer. In this paper, thermoplastic starch acetate (TPAS) and maleic anhydride grafted poly[styrene-b-(ethylene-co-butylene)-b-styrene] (SEBS-MAH) were used to toughen polypropylene (PP) through melt blending. It is found TPAS and SEBS-MAH have a synergistic toughening effect on PP, especially the notched impact strength of PP/TPAS/SEBS-MAH (70/15/15) blend is as high as 83.4 kJ/m 2 , but only 7.2 kJ/m 2 of that for PP/TPAS/SEBS (70/15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…For example, the core–shell structure of toughened PP can use PE as the core and EPR as the shell, , silicon dioxide-EPDM core–shell particles, and so on. The addition of core–shell particles and the formation of a ternary blend system, according to the theoretical model proposed by Wu, can simultaneously improve the toughness and reduce the modulus loss in composite materials. Meanwhile, the particular core–shell structure provides more possibilities in selecting the core and shell. As a typical two-phase modifier, it opens a new path for designing and synthesizing stiffness–toughness balanced materials. Pure inorganic particles have a reinforcing effect on thermoplastic materials, but they do not significantly improve toughness. To decrease stiffness loss and increase toughness, the preferred method is to use core–shell structures consisting of inorganic particles and elastomers or rubbers to modify thermoplastic polymers.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the core–shell structure of toughened PP can use PE as the core and EPR as the shell, , silicon dioxide-EPDM core–shell particles, and so on. The addition of core–shell particles and the formation of a ternary blend system, according to the theoretical model proposed by Wu, can simultaneously improve the toughness and reduce the modulus loss in composite materials. Meanwhile, the particular core–shell structure provides more possibilities in selecting the core and shell. As a typical two-phase modifier, it opens a new path for designing and synthesizing stiffness–toughness balanced materials. Pure inorganic particles have a reinforcing effect on thermoplastic materials, but they do not significantly improve toughness. To decrease stiffness loss and increase toughness, the preferred method is to use core–shell structures consisting of inorganic particles and elastomers or rubbers to modify thermoplastic polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies showed the excellent toughening effect of SEBS in polymer blends. [24][25][26] Jiang et al studied the flame retardant mechanism of SEBS/PPO blends and showed that SEBS could improve their thermal stability by incorporating PPO. 27 Tang et al studied the synergistic reinforcement and toughening of PPO/HIPS materials with GFs as a reinforcing agent and polystyrene butadiene block (SEBS) as a toughening agent.…”
Section: Introductionmentioning
confidence: 99%